The influence of aquifer material to the groundwater potency in Ngawi Regency - Setyawan Purnama Ignasius Loyola (EDP Sciences, 2021)
Until now, groundwater is still the main source of water for domestic needs. Unfortunately not all places can contain groundwater. Groundwater potential in an area is largely determined by the rock layers that make up the aquifer in the area. This study aims to analyze the hydrogeological conditions of the study area and to analyze the potential for groundwater in each geological unit. To achieve this goal, this study is based on the analysis of existing secondary data, such as rock type data obtained from drill data and geological maps. Apart from these data, the main secondary data from this research is geosonar measurement data that has been done previously. In this geosonar estimation, VLF (Very Low Frequency) electromagnetic technology is used, which is a geophysical method that uses very low radio communication frequency signals (15-30 kHz) to determine the anomalies of the electrical properties of rocks. The results showed that hydrogeologically, Ngawi Regency can be divided into two, namely areas with high groundwater potency in the central and southern parts and areas with rare groundwater in the northern part. In addition, it is also known that there is a relationship between the aquifer material and the groundwater potency. Alluvial deposits which are dominated by sand and gravel have high groundwater potency, while the Kalibeng Formation which is composed of solid marl and Anggota Banyak Kalibeng Formation composed of andesite breccias is a scarce groundwater area.